2016
DOI: 10.4062/biomolther.2015.113
|View full text |Cite
|
Sign up to set email alerts
|

Cytisine, a Partial Agonist of α4β2 Nicotinic Acetylcholine Receptors, Reduced Unpredictable Chronic Mild Stress-Induced Depression-Like Behaviors

Abstract: Cytisine (CYT), a partial agonist of α4β2-nicotinic receptors, has been used for antidepressant efficacy in several tests. Nicotinic receptors have been shown to be closely associated with depression. However, little is known about the effects of CYT on the depression. In the present study, a mouse model of depression, the unpredictable chronic mild stress (UCMS), was used to evaluate the activities of CYT. UCMS caused significant depression-like behaviors, as shown by the decrease of total distances in open f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…A growing body of evidence suggests that severe stress can suppress BDNF signaling, impair synaptic activity and increase susceptibility to affective disorders, resulting in neuronal atrophy and cognitive impairment [ 45 ]. Several evidence indicate that chronic stress and low level of BDNF are the major components of sickness behavior [ 46 ]. In this study, surgical trauma in combination with CUS inhibited BDNF expression in the brain, which was accompanied with sickness behavior.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggests that severe stress can suppress BDNF signaling, impair synaptic activity and increase susceptibility to affective disorders, resulting in neuronal atrophy and cognitive impairment [ 45 ]. Several evidence indicate that chronic stress and low level of BDNF are the major components of sickness behavior [ 46 ]. In this study, surgical trauma in combination with CUS inhibited BDNF expression in the brain, which was accompanied with sickness behavior.…”
Section: Discussionmentioning
confidence: 99%
“…There is a high systemic bioavailability of cytisine in healthy smokers taking this drug for smoking cessation, albeit with mild adverse reactions ( Hajek et al, 2013 ). Accumulating evidence has shown that cytisine has neuroprotective effects in some neurological diseases such as Parkinson’s disease, depression, and cerebral injury induced by ischemia-reperfusion in animal models ( Abin-Carriquiry et al, 2008 ; Han et al, 2016 ; Zhao et al, 2018 ). However, whether cytisine plays a role in the treatment of chronic spontaneous epilepsy remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Decreasing alpha-4 beta-2 activity, whether through antagonism or desensitization, reduces inhibitory neuron activity and increases dopamine release, which increases NAc plasticity downstream. However, there is evidence that alpha7 nAChR stimulation induces depressive symptoms [76] and cytisine, a selective alpha-4 beta-2 partial agonist, which is consistent with the NAc plasticity model [77]. However, there is contradictory evidence that alpha7 nAChR knockout induced depressive symptoms and increased NAc synaptogenesis and BDNF levels [78].…”
Section: Functional Annotation Clusteringmentioning
confidence: 83%